Hydrometallurgical Simulation - A Viable Program Structure - Cilliers, Johannes Jacobus Le Roux (My University, 2015)
In order to satisfy the increasingly sophisticated requirements for simulation in the metallurgical industry, this research focused on the development of data structures and algorithms general and extendable enough to accomodate all hydrometallurgical processes. The data structures' designed to describe process stream information were based on the concept of sub-streams (Britt-, 19SG) using the pi ex data structure (Evans, Joseph and Seider, 1977) inherent to the Pascal programming language. As sub-streams are combined to describe complete process streams, the data structures may be extended to describe any process stream by creating additional sub-streams as may be required. Algorithms for partitioning, tearing and ordering flow sheets based on the work of Tarjan (1972, 1973) and Lee and Rudd (1966) were designed and implemented. These algorithms are able to treat the large problem sizes associated with hydrometallurgical process flow sheets. The data structures and algorithms have been successfully combined into a powerful process simulator extendable to the general hydrometallurgical process description.